(untitled) (Global Journal of Science Frontier Research, 2025)
This paper presents an incontrovertible, fact-based framework that fundamentally challenges the age-old assumptions of classical mechanics, particularly the notions of absolute time and space. We demonstrate, with mathematical rigor and empirical clarity, that these assumptions do not hold when subjected to rigorous analysis of real-world phenomena, especially under extreme conditions. Our new model of space, time, and motion provides a correct, reliable, and comprehensive understanding of the universe -one that aligns seamlessly with the most accurate observations and leaves no room for doubt. Through this work, we reshape our understanding of the cosmos and offer humanity an unshakable foundation for future advancements in science.